Analisis Yuridis Terhadap Penegakan Hukum Pelanggaran Lalu Lintas Dan Angkutan Jalan Berdasarkan Electronic Traffic Law Enforcement (ETLE) Dalam Kaitan Prinsip Sanksi Pidana Hanya Dapat Dijatuhkan Melalui Proses Peradilan - Ahmad Gazali (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine the application of Electronic Traffic Law Enforcement (ETLE) and to determine the implementation of the principle of criminal sanctions that can only be imposed through court decisions in the law enforcement proceeding of traffic violations based on Electronic Traffic Law Enforcement (ETLE). This research is Normative Legal Research in which researchers will collect and review primary data on the law enforcement proceeding of ETLE violation along with secondary data in the form of primary, secondary, and tertiary legal materials. The results indicate that the implementation of ETLE is regulated by various laws and regulations including Act No. 22/2009 on Traffic and Transportation; Government Regulation No. 80/2012 on Procedures for Inspection of Motorized Vehicles on the Road and Enforcement of Traffic and Road Transportation Violations in conjunction with Chief of Police Regulation No. 5/2012 on Registration and Identification of Motorized Vehicles in conjunction with The Supreme Court Regulation No. 12/2016 on Procedures for Settlement of Traffic Violations Cases and there is no visible contradiction or disharmony. However, in the application of these regulations there are indications of disharmony between the law and their implementation and law enforcement, where violators entrust payment of fines that have been adjusted to the number of fines that will later be will be decided by a court judge, even though if referring to Article 267 Paragraph (4) of the Traffic Act, the amount of money deposited is equal to a maximum fine of the criminal penalty.